PELATIHAN AKUNTANSI PEPAJAKAN UNTUK MEMASUKI DUNIA KERJA DI SMAN 1 KOPO - Sugiyono Sugiyono; Abu Naim; Rosidawaty Rosidawaty; Rina Ambarwati; Ingkak Chintya Wangsih; Andika Mugi Gumilang; Dadang Dadang; Sena Atmaja; Helmas Septiyo Hadi; Dindin Aminudin; Ahmad Pauji (Universitas Mataram, 2025)
High school graduates need to have practical skills, especially in tax accounting, due to changes in the world of work. Many students are still confused about proper financial record-keeping and tax administration. Because of this situation, they are not prepared to meet the skill requirements needed by the industry. Therefore, SMAN 1 Kopo needs tax accounting training to provide students with relevant and practical skills. The community service activity